Factors affecting the attitude of librarians towards research in library and information science: a case study of Imo State, Nigeria (2011)
This work is about factors affecting the attitude of librarians, especially in Imo State, to Library and Information Science (LIS) research. The purpose of the study is to determine whether the research contributions of librarians in the State in terms of published works are really significant or not; to identify' constraints to LIS research and suggest solution to the lack of research publications o f librarians in the State. The work delved on the history of LIS research in Nigeria from the colonial era till date after which relevant literatures were reviewed. Survey research method was used for the study and three research questions were formulated as a guide for the study. The target population is the total number of Librarians in academic libraries in Imo State, which is seventy five (75) in this instance. Since the population is not too large, the total population was purposively used and no sampling was required. Questionnaire was the main instrument used for data collection; hence, seventy five (75) copies of the questionnaire were given out to all the librarians in the State. Sixty (60) of the librarians participated in the research and duly filled and return their questionnaire (representing 80% rate of return). Data so collected were analyzed descriptively, while research findings were presented in tables and discussed. It was found that majority of the librarian in Imo State are not publishing. Also, among the constraints to LIS researches as perceived by the respondents are: lack of mentoring or inability to find someone to help in “breaking the ice ”; low level of author collaboration; negative altitude to quantitative techniques; terminating academic work at either 1st/ 2nd degree level that may not have been research based in the first instance; lack of time because of heavy workload and the rigidity of library procedures; lack of relevant / current library resources available where librarians are working and lack of or inadequacy of personal library of LIS books and journals. However, the study concluded and made recommendations on how the LIS research efforts of librarians in the Stale can he enhanced.